1989
DOI: 10.1038/ki.1989.232
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and glomerular hemodynamics in male endotoxemic rats

Abstract: The renal effects of a single intravenous dose of two different E. coli lipopolysaccharides (LPS 0111:B4 and LPS 0127:B8), at the same dose of 100 micrograms/kg, were evaluated in euvolemic Munich-Wistar (MW) rats by whole kidney clearance techniques and micropuncture studies. Following LPS infusion, a significant decrease (8%) in mean BP was observed only in the LPS 0127:B8 treated group. Inulin clearance fell 57% (LPS 0111:B4), P less than 0.01, and 38% (LPS 0127:B8), P less than 0.01. Para-aminohippuric (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 17 publications
4
56
1
Order By: Relevance
“…Despite the accompanying hypotension, we found a marked renal vasoconstriction during endotoxemic shock, a finding implicating active involvement of vasoactive factors. Our results showing renal vasoconstriction and increased RVR agree with previous in vitro and in vivo studies in rodents (5,6,10).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite the accompanying hypotension, we found a marked renal vasoconstriction during endotoxemic shock, a finding implicating active involvement of vasoactive factors. Our results showing renal vasoconstriction and increased RVR agree with previous in vitro and in vivo studies in rodents (5,6,10).…”
Section: Discussionsupporting
confidence: 83%
“…However, both in experimental models of sepsis and in patients, changes in renal blood flow (RBF) vary widely. Micropuncture studies of renal hemodynamics during endotoxin infusion have shown that GFR and glomerular plasma flow are reduced, primarily as a result of increased afferent arteriolar resistance (5). Other studies show that intraluminal application of LPS in a bloodperfused juxtamedullary nephron preparation elicits a sustained vasoconstriction of the arcuate artery, interlobular artery, and afferent arteriole, without affecting efferent arteriolar diameter.…”
mentioning
confidence: 96%
“…Cyclooxygenase inhibition with indomethacin had a markedly protective effect on glomerular hemodynamics in endotoxemic rats (77). A selective thromboxane synthetase inhibitor attenuated the renal effects of LPS in the rat (78) and protected the kidney in sheep with hyperdynamic septic shock (79).…”
Section: Inhibitors Of Arachidonic Acid Metabolismmentioning
confidence: 99%
“…[2][3][4][5] The causative contribution of renal blood flow (RBF) to kidney dysfunction is particularly puzzling in sepsis, and there is widespread disagreement as to whether RBF is reduced, normal, or even increased. 2,3,[6][7][8] In the few large animal and clinical studies, the patterns of RBF in AKI and its relation with systemic hemodynamics are highly variable. 3,6 Absence of benefit of vasodilator therapy in human sepsis-associated AKI 9 may be explained by variability in blood flow.…”
Section: Total Renal Blood Flow In Akimentioning
confidence: 99%